2003
DOI: 10.1037/0893-3200.17.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Conflict, social support and relationship quality: An observational study of heterosexual, gay male and lesbian couples' communication.

Abstract: Data from 42 heterosexual, 46 gay male, and 33 lesbian couples were used to assess the contribution of conflict and support discussions to relationship quality. Couples completed questionnaires, and videotaped discussions were coded for levels of negative and positive behaviors. Correlations showed that behaviors were associated with relationship quality in the expected directions. Hierarchical linear modeling analyses assessed the unique contributions of individual and dyadic behaviors to the variability of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 51 publications
11
88
2
4
Order By: Relevance
“…This type of finding is consistent with the results of the few previous studies that have examined the interplay between conflict and support in marriage (Julien, Chartrand, Simard, Bouthillier, & Bégin, 2003;Pasch & Bradbury, 1998;Verhofstadt et al, 2005).…”
Section: Summary Of Resultssupporting
confidence: 82%
“…This type of finding is consistent with the results of the few previous studies that have examined the interplay between conflict and support in marriage (Julien, Chartrand, Simard, Bouthillier, & Bégin, 2003;Pasch & Bradbury, 1998;Verhofstadt et al, 2005).…”
Section: Summary Of Resultssupporting
confidence: 82%
“…Sexual satisfaction and positive communication styles were significantly related to partner satisfaction (Litzinger & Gordon, 2005). Julien, Chartrand, Simard, Bouthillier, and Bégin (2003) found that communication styles in conflict and support situations were correlated with relationship quality, with negative styles of com munication having lower levels of satisfaction and positive styles of communication reporting higher levels of satisfaction. They concluded that aside from the negative and positive behaviors in conflict and support tasks, variance in relationship satisfac tion is responsive to the influence of both partners' involvement in a task (Julien et al, 2003).…”
Section: Relationship Satisfactionmentioning
confidence: 86%
“…Some of those other factors may include commu nication or equity. Other studies have shown that communication influences relationship satisfaction (Julien et al, 2003;Litzinger & Gordon, 2005). Positive communication styles, especially in situa tions involving conflict, are related to higher levels of relationship satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, we have never even argued about this.'' Research indicates that, across various outcomes such as communication style, and gender and labor roles, gay and lesbian relationships tend to be performed in ways that are more equitable than is recorded in many heterosexual relationships (Julien et al 2003;Patterson 2000) and that, in terms of relationship satisfaction, it is often difficult to find meaningful differences between same-sex and other-sex relationships (Peplau et al 1996). Although couples in the current sample expressed concern over some dimension of their relationship, most also reported they extracted positive meaning from their experience with their partner and equated their relationship to the importance of well-established, familial and religiously-sanctioned relationships.…”
Section: Power Dynamics Within a Partnered Relationshipmentioning
confidence: 97%